Answer:
2561.2785
Step-by-step explanation:
Answer:
x=1, y=7
Step-by-step explanation:
y = -3x + 10 - first equation
y=-3x + 4 - second equation
rearrange the expression to
-3x-y= -10
3x-y= -4
pick an equation and simplify; lets pick the second equation
3x-y= -4
divide 3 by both sides
x=
- third equation
substitute the value of x into an equation; lets pick the first equation
-3x-y= -10
-3
- y = -10
simplify. -3 cancels 3 so we are left with
-1(-4+y)-y = -10
simplify
4-y-y= -10
4-2y= -10
subtract 4 from both sides
-2y= -10-4
-2y= -14
divide -2 by both sides
y=7
substitute the value of y, (y=7) in an equation, we are using the second equation
3x-y= -4
3x-7= -4
3x = -4+7
3x= 3
divide 3 by both sides
x=1
so the answer is x=1, y=7
Step-by-step explanation:
5(x + 9) = 5*x + 5*9
which is
5x + 45
Answer: 23.70
Step-by-step explanation:
Because 3.95x6=23.70